1993
DOI: 10.1002/j.1460-2075.1993.tb05858.x
|View full text |Cite
|
Sign up to set email alerts
|

Integration of murine leukemia virus DNA depends on mitosis.

Abstract: In synchronized rat or mouse cells infected with Moloney murine leukemia virus (MLV), integration of viral DNA and production of viral proteins occur only after the cells traverse mitosis. Integration is blocked when cells are prevented from progressing through mitosis. Viral nucleoprotein complexes isolated from arrested cells contain full‐length viral DNA and can integrate this viral DNA in vitro, showing that the block to integration in arrested cells is not due to a lack of mature integration machinery. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
634
0
4

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 875 publications
(661 citation statements)
references
References 58 publications
23
634
0
4
Order By: Relevance
“…In our particular case, it is important to remember that MMTV, as most retroviruses, can insert only in division competent cells. 26,27 Second, these cells could be committed not only to a secretory phenotype, but also to the secretion of a particular protein. Robinson et al 28 showed that the different pattern of expression of WAP and ␤-casein during mammary development suggests the possibility of different secretory cells committed to express either one of these proteins.…”
Section: High Expression At the Wap Promoter In Mmtv-induced Tumors Gmentioning
confidence: 99%
“…In our particular case, it is important to remember that MMTV, as most retroviruses, can insert only in division competent cells. 26,27 Second, these cells could be committed not only to a secretory phenotype, but also to the secretion of a particular protein. Robinson et al 28 showed that the different pattern of expression of WAP and ␤-casein during mammary development suggests the possibility of different secretory cells committed to express either one of these proteins.…”
Section: High Expression At the Wap Promoter In Mmtv-induced Tumors Gmentioning
confidence: 99%
“…One of these strategies is to anchor pDNA to the chromatin during cell division, so that the nanoparticles efficiently are enclosed in the nuclei of the daughter cells. This strategy is in fact used by some retroviruses and some latent DNA viruses taking advantage of mitosis [10][11][12][13]. Binding of DNA or DNA nanoparticles to chromatin could both enhance the nuclear inclusion and increase the probability that pDNA is passed on during subsequent cell divisions.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 A major limitation of the currently available retroviral vectors is their requirement for target cells to transit the cell cycle in order for proviral integration to occur. 12,13 Mobilised peripheral blood stem cells are generally quiescent and are thus intrinsically refractory to transduction by such vectors. 14 Attempts to improve transduction efficiency by using cocktails of haemopoietic growth to induce entry into the cell cycle resulted in only transient marking of cells in vivo, suggesting that retroviral integration had occurred in committed progenitors rather than stem cells.…”
Section: Introductionmentioning
confidence: 99%